Effects of physical exercise on inflammatory parameters and risk for repeated acute coronary syndrome in patients with ischemic heart disease - Ranković Goran; Miličić Branislava; Savić Todorka; Đinđić Boris; Mančev Zorica; Pešić Gordana (Vojnosanitetski Pregled)
Background/Aim. Inflammation is an important factor in the pathogenesis of atherosclerosis, and several markers of inflammation have been associated with an increased risk of cardiovascular events. Physical activity may lower the risk for coronary heart disease (CHD) by mitigating inflammation. The aim of this study was to investigate the effects of aerobic physical exercise on systemic inflammatory response in patients with stable coronary disease participating in a cardiovascular rehabilitation exercise program. Methods. Male (n = 29) and female (n = 23) patients with stable coronary heart disease were enrolled in this study. All the patients were divided into two groups: the group with regular aerobic physical training during cardiovascular rehabilitation program phase II for 3 weeks in our rehabilitation center and 3 weeks after that in their home setting, and sedentary lifestyle group. There were no significant differences in gender distribution among the analyzed groups. Student's t-test showed no significant differences in average age, waist circumference (OS) and waist/hip ratio (WHR). Results. The degree of obesity was measured by BMI and there was a significant improvement in BMI in the patients who undertook 6-week physical training compared to the controls (p < 0.05). Physical training during 6-week appeared not to have any effects on leukocite count and ICAM-1 levels compared to controls. Exercise induced reduction in plasma CRP levels by 23.72% (p < 0.001) and reduction in plasma VCAM-1 levels by 10.23%, (p < 0.05). Conclusion. Moderate aerobic exercise resulted in a significant reduction of inflammatory state by decreasing CRP and VCAM-1 levels with significant obesity reduction but without visceral obesity reduction. The obtained results indicate that regular physical activity is clinically desirable in primary and secondary prevention of coronary heart diseases.